Exoneration Clauses and Contractual Justice in Hospitality Service Agreements - Sayu Putu Nia Kumala Yanti; Ni Komang Arini Styawati; Anak Agung Istri Agung (PT Inovasi Pratama Internasional, 2026)
The increasing use of standardized service agreements in the hospitality industry has intensified reliance on exoneration clauses as mechanisms for allocating legal risks and limiting liability. While such clauses are generally justified under the principle of freedom of contract, their application may undermine contractual justice when bargaining positions are unequal. This study examines the legal regulation, characteristics, and implementation of exoneration clauses in hospitality service agreements under Indonesian contract law and evaluates their compatibility with the principles of balance, good faith, and fairness. Using normative legal research with statutory, conceptual, and case approaches, legal materials were analyzed through systematic, grammatical, and teleological interpretation. The findings indicate that exoneration clauses are legally permissible provided they do not excessively exclude liability or disrupt contractual equilibrium. However, the examined service agreement demonstrates that limitation of liability and indemnification provisions predominantly transfer legal risks to the local service provider, reflecting a significant bargaining imbalance. The novelty of this study lies in its analysis of contractual justice within business-to-business relationships in the international hospitality sector. The study concludes that freedom of contract must be exercised proportionately to preserve fairness. Future research should undertake comparative studies across jurisdictions and hospitality business models to develop more balanced risk-allocation standards.